Conductive and photoactive nature of conjugated polymer based on thiophene functionalized thiazole or benzothiadiazole - K. Mahesh; S. Karpagam; F. Goubard (eXPRESS Polymer Letters, 2018)
New poly (thiophene vinyl thiazole) (PTVT) and poly (thiophene vinyl benzothiadiazole) (PTVBT) was synthesized by Wittig condensation route. The absorption maximum of PTVT and PTVBT appeared at 376 and 410 nm in a solution state, and it was red-shifted to 417 and 510 nm in a thin film state. The optical band gaps were 1.7 and 1.5 eV calculated from thin film absorption edges of the polymer. The photoluminescence spectra of PTVT and PTVBT have an emission peak at 457 nm with bluish green and 487 nm with greenish-yellow fluorescence in THF solution. Both polymers showed a short fluorescence decay time (τ1) of 2.31 and 0.73 ns respectively. Furthermore, the aggregation-caused quenching (ACQ) phenomenon observed in both polymers in decreased fluorescence intensity with different water fractions. The lower electrochemical band gaps were achieved for both polymers (1.4, and 1.3 eV) from cyclic voltammetry. Both polymers have a granular shaped morphology with good surface roughness was observed using AFM. High thermal stability was observed with 8% weight loss at 400 °C for PTVT and 6% weight loss at 460°C for PTVBT. The highest electrical conductivity was observed from electrochemical impedance measurement which was 7.68·10–6 Ω–1·cm–1 for PTVBT.